Importance of Serum Ferritin Level for Early Diagnosis and Differentiation in Patients with Kawasaki Disease with Macrophage Activation Syndrome - Da Eun Roh; Jung Eun Kwon; Hee Joung Choi; Yeo Hyang Kim (MDPI AG, 2021)
We aimed to evaluate the utility of the serum ferritin level as an early screening test of Kawasaki disease with macrophage activation syndrome (KD-MAS). We analyzed the serum ferritin levels on the first day of admission and the clinical progress of patients diagnosed with complete or incomplete KD. Of the 158 patients, 5 were diagnosed with KD-MAS. Conjunctival injection was significantly more frequent in KD group (p = 0.035), although there were no significant differences in other clinical features. On the first day of admission, the serum ferritin level in the KD-MAS group was >500 ng/mL, which was higher than that in the KD group (p = 0.001). In the KD-MAS group, total bilirubin, triglyceride, and lactate dehydrogenase (LDH) were significantly higher, and erythrocyte sedimentation rate (ESR), total protein, albumin, and fibrinogen were significantly lower than the KD group (p < 0.05). Four patients were diagnosed with MAS within 7 days after admission, and 4 (80%) patients with KD-MAS survived. In conclusion, carrying out an early ferritin screening test is important in patients with principal clinical features that may suspect KD. We propose to include ferritin level in the primary laboratory test to differentiate between KD with and without MAS early.